2020
DOI: 10.1111/pace.13924
|View full text |Cite
|
Sign up to set email alerts
|

SCN5A mutation identified in a patient with short‐coupled variant of torsades de pointes

Abstract: Background: Short-coupled variant of torsades de pointes (scTdP) is a disease characterized by TdP without QT prolongation, which is initiated by extremely short-coupled ventricular extrasystoles. Its genetic background remains rarely unveiled. Objective:We aimed to identify genetic variations in patients with scTdP and to analyze the functional change of the mutant Na + channel identified in a scTdP patient. Methods and results:We performed genetic analysis for inherited arrhythmia-related 45 genes using next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Genetic analysis conducted by Touat-Hamici et al [32] showed that RYR2 variant I748F in SPRY1 may be pathogenic, changing the thermal stability of the SPRY1 domain, leading to spontaneous Ca 2+ release and further VA. Other RYR2 variants reported to be associated with scTdP are RyR2-V1024I, RyR-N1151S, RyR2-S4938F, RyR2-M995V, and RyR2-H29D [33][34][35]. Finally, Sonoda et al [36] identified an SCN5A mutation in a patient with scTdP. It should be noted that all variants above require further assessment, whereas currently available data suggest a potential genetic basis for scTdP.…”
Section: Early Afterdepolarization (Ead)mentioning
confidence: 99%
“…Genetic analysis conducted by Touat-Hamici et al [32] showed that RYR2 variant I748F in SPRY1 may be pathogenic, changing the thermal stability of the SPRY1 domain, leading to spontaneous Ca 2+ release and further VA. Other RYR2 variants reported to be associated with scTdP are RyR2-V1024I, RyR-N1151S, RyR2-S4938F, RyR2-M995V, and RyR2-H29D [33][34][35]. Finally, Sonoda et al [36] identified an SCN5A mutation in a patient with scTdP. It should be noted that all variants above require further assessment, whereas currently available data suggest a potential genetic basis for scTdP.…”
Section: Early Afterdepolarization (Ead)mentioning
confidence: 99%